Impacts of conventionally-treated and additionally ozonated wastewater on mortality, biochemical markers, and locomotor activity of two aquatic insect species: Leuctra geniculata (Plecoptera) and Hydropsyche incognita (Trichoptera) - Louisa E. Rothe; Nazmun Nahar; Robin Stift; Almut Gerhardt; Michael Weyand; Daniel Grabner; Christian K. Feld; Bernd Sures (Environmental Pollution, 2026)

Locomotor activity and physiological responses of parasite-infected Gammarus fossarum exposed to the herbicide metazachlor - Nazmun Nahar; Ipsita Sarkar; Sebastian Prati; Louisa E. Rothe; Daniel Grabner; Sonja Zimmermann; Anam Asghar; Torsten C. Schmidt; Bernd Sures (Environmental Pollution, 2025)

Influence of salinity on the thermal tolerance of aquatic organisms - Luan Farias; Bánk Beszteri; Andrea M. Burfeid Castellanos; Annemie Doliwa; Julian Enss; Christian K. Feld; Daniel Grabner; Kathrin P. Lampert; Ntambwe A. Serge Mayombo; Sebastian Prati; Christian Schürings; Esther Smollich; et al. (Science of The Total Environment, 2024)

Metacollinia emscheri n. sp., a novel sanguicolous apostome ciliate of freshwater amphipods (Gammarus spp.) - Sebastian Prati; Sonja Rückert; Daniel S. Grabner; Bernd Sures; Jamie Bojko (Journal of Invertebrate Pathology, 2024)

Why renovation obligations can boost social justice and might reduce energy poverty in a highly decarbonised housing sector - Andreas Müller; Marcus Hummel; Koen Smet; Daniel Grabner; Katharina Litschauer; Irma Imamovic; Fatma Ece Özer; Lukas Kranzl (Energy Policy, 2024)

Invisible invaders: range expansion of feral Neocaridina davidi offers new opportunities for generalist intracellular parasites - Sebastian Prati; Daniel S. Grabner; Kamil Hupało; András Weiperth; Rafał Maciaszek; Boris Lipták; Jamie Bojko; Fanni Bérces; Bernd Sures (Biological Invasions, 2024)
The release of ornamental pets and associated pathogens outside their native range might directly or indirectly impact the recipient community. In temperate regions, e.g., central Europe, feral freshwater species of tropical and sub-tropical origins are mainly constrained to thermally polluted waters and thermal springs. However, species with high environmental plasticity and reproduction rates, such as the shrimp Neocaridina davidi , may adapt to colder water regimes over time. A widening thermal niche may eventually overcome thermal barriers, further expanding the range and enhancing transmission opportunities for host generalist parasites. This study assesses the observed (field observations) and theoretical (species distribution models) range expansion of N. davidi and associated parasites in Europe. We report three newly established N. davidi populations from thermally polluted waters in central Europe (Germany, Hungary, and Slovakia) and provide further evidence of its range expansion into colder environments. Species distribution models predict thermally suitable habitats in the Mediterranean and a foreseeable expansion into Western Europe and the Balkans by 2050. We confirm the presence of the microsporidian parasite Ecytonucleospora hepatopenaei in feral N. davidi populations across Europe and expand the list of microsporidians found in this host from two to four. Furthermore, we provide the first evidence of parasite spillover from/to the invasive crayfish Procambarus clarkii, suggesting that parasite exchange with native biota might be possible. Such possibility, coupled with an ongoing range expansion of N. davidi bolstered by human-mediated introductions and climate change, will likely exacerbate the impact on native biota.

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Parasitism enhances gastropod feeding on invasive and native algae while altering essential energy reserves for organismal homeostasis upon warming - Dakeishla M. Díaz-Morales; Claudia Bommarito; Jeffrey Knol; Daniel S. Grabner; Simona Noè; Gil Rilov; Martin Wahl; Tamar Guy-Haim; Bernd Sures (Science of The Total Environment, 2023)

Pollutant load and ecotoxicological effects of sediment from stormwater retention basins to receiving surface water on Lumbriculus variegatus - Julios Armand Kontchou; Nicolai Baetz; Daniel Grabner; Milen Nachev; Jochen Tuerk; Bernd Sures (Science of The Total Environment, 2023)

The trematode Podocotyle atomon modulates biochemical responses of Gammarus locusta to thermal stress but not its feeding rate or survival - Dakeishla M. Díaz-Morales; Maral Khosravi; Daniel S. Grabner; Nazmun Nahar; Claudia Bommarito; Martin Wahl; Bernd Sures (Science of The Total Environment, 2023)